2022
DOI: 10.1101/2022.12.19.520972
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intramolecular autoinhibition of human PEX13 modulates peroxisomal import

Abstract: Targeting and import of peroxisomal proteins depends on PEX5, PEX14 and PEX13. We present a biochemical and structural characterization of the PEX13 C-terminal region. By combining NMR spectroscopy, X-ray crystallography and biochemical methods, we show that the PEX13 SH3 domain mediates intramolecular interactions with a newly identified proximal FxxxF motif and also binds to WxxxF peptide motifs from the PEX5 NTD, demonstrating evolutionary conservation of this interaction from yeast to human. Strikingly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 77 publications
0
0
0
Order By: Relevance
“…In this model, first, the WxxxF/Y motif of PEX5L binds to the NTD of PEX14 with strong affinity. This is then replaced by binding of the PEX13 FxxxF motif to the NTD PEX14 and PEX13 SH3 domain to the PEX5 NTD, which possibly requires large amounts of PEX13 due to their weak affinities for both PEX5 and PEX14 (Gaussmann et al 2022). Supporting this, the detection of a large molecular mass complex that exclusively consists of PEX13 or PEX13/PEX14 has been reported already (Ravindran et al 2023;Gao et al 2022;Itoh and Fujiki 2006).…”
Section: Pex13 As Part Of the Transloconmentioning
confidence: 88%
See 4 more Smart Citations
“…In this model, first, the WxxxF/Y motif of PEX5L binds to the NTD of PEX14 with strong affinity. This is then replaced by binding of the PEX13 FxxxF motif to the NTD PEX14 and PEX13 SH3 domain to the PEX5 NTD, which possibly requires large amounts of PEX13 due to their weak affinities for both PEX5 and PEX14 (Gaussmann et al 2022). Supporting this, the detection of a large molecular mass complex that exclusively consists of PEX13 or PEX13/PEX14 has been reported already (Ravindran et al 2023;Gao et al 2022;Itoh and Fujiki 2006).…”
Section: Pex13 As Part Of the Transloconmentioning
confidence: 88%
“…This implies that it can also act as a bait component for the PEX5 receptor in the cytosol and bring it inside the matrix. Supporting this hypothesis, it was recently shown that the C-terminal SH3 domain of human PEX13 binds WxxxF/Y motifs in the PEX5L NTD (Gaussmann et al 2022). The same group also found a novel FxxxF peptide motif in the C-terminal region SH3 domain of human PEX13, whose binding has an autoinhibitory effect (Gaussmann et al 2022).…”
Section: Pex13 As Part Of the Transloconmentioning
confidence: 90%
See 3 more Smart Citations